(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper present one decision on innovation European industry contributes to output, jobs, innovation and exports and is interrelated with service industries. Indeed, many service industries such as transport, health and Information and Communication Technologies (ICT) depend on competitive industry to produce the equipment and hardware which they use [1, 2].